2018
DOI: 10.1111/jcmm.13892
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAPCAT1 targeting miR‐145‐5p promotes TLR4‐associated osteogenic differentiation of adipose‐derived stem cells

Abstract: This study was aimed to explore the differential expression of long noncoding RNAs (lncRNA)‐PCAT1, miR‐145‐5p and TLR4 in osteogenic differentiation via the Toll‐like receptor (TLR) signalling pathway and consequently determine the potential molecular mechanism. The mRNAs and pathways related to the osteogenic differentiation in human adipose‐derived stem cells (hADSCs) were analysed by bioinformatics. The MiRanda and TargetScan database were employed to detect the potential binding sites of miRNAs on lncRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…In addition, another pathway explored was the toll-like receptor (TLR) signaling pathway. Using similar strategies to previous study ( Wu et al, 2018 ), Yu et al (2018) observed an interaction between TLR4 (upregulated in osteogenesis) with lncRNA-PCAT1 and miR-145-5p, which were able to regulate the TLR pathway.…”
Section: Gene Expression Profile In Osteogenesis Of Mscsupporting
confidence: 57%
“…In addition, another pathway explored was the toll-like receptor (TLR) signaling pathway. Using similar strategies to previous study ( Wu et al, 2018 ), Yu et al (2018) observed an interaction between TLR4 (upregulated in osteogenesis) with lncRNA-PCAT1 and miR-145-5p, which were able to regulate the TLR pathway.…”
Section: Gene Expression Profile In Osteogenesis Of Mscsupporting
confidence: 57%
“…Emerging studies have demonstrated the increasing vital roles of noncoding RNAs (ncRNAs) in the human diseases, especially cancers . For the glioma, conservatively, hundreds of lncRNAs have been reported to participate in the cellular processes modulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well-documented that many non-coding RNAs can targetedly regulate specific TLRs, and thus contribute to the development of RA, including lncRNAs (15, 16, 30). Many studies have implicated the critical role of lncRNAs in regulating autoimmune and inflammation by targeting TLRs, such as TLR2, TLR4, and TLR3 (3537). Most interestingly, more and more published studies have suggested that some established lncRNAs can regulate TLR signaling transduction and the relevant immune function in cancer, autoimmune and inflammatory disorders by acting as ceRNAs, such as networks of lncRNA SNHG1-miR-140-TLR4, lncRNA X-miR-154-5p-TLR5, and lncRNA Gm6135-miR-203-3p-TLR4 (3841).…”
Section: Discussionmentioning
confidence: 99%